2016
DOI: 10.25200/bjr.v12n3.2016.895
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the Boundaries: The Interpretative Repertoires Journalists Use to Differentiate Themselves from the Public Relations Industry

Abstract: RESUMO-Os jornalistas recorrem a diversos repertórios interpretativos para descrever a sua relação com a indústria das RP. Estes incluem discursos institucionais tanto do seu campo como dos seus congéneres das RP. Os jornalistas usam ainda o código deontológico da sua profissão à medida da sua conveniência. Por fim, exploram um repertório a que aqui chamamos de discurso "realista". Os jornalistas podem mobilizar numa única frase os vários repertórios interpretativos, o que ilustra as complexidades no âmago da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…An examination of public relations practitioners seeking to book political clients onto TV news shows in the Netherlands found that they drew on interpretive repertoires related to play, positioning their interactions with journalists as a strategic balance between struggle and cooperation (Schohaus, Broersma, and Wijfjes 2017). Conversely, Francoeur (2016) found that Canadian journalists tap into multiple interpretive repertoires in articulating the ways in which they believe themselves to be different from public relations practitioners. Looking at the interpretive resources on which New Zealand journalists draw in writing about Maori people and issues, Matheson (2007, 93) identified a limited range, "repertoires of prejudice" difficult to overcome.…”
Section: How Journalists Talk About Journalism (And Themselves)mentioning
confidence: 94%
“…An examination of public relations practitioners seeking to book political clients onto TV news shows in the Netherlands found that they drew on interpretive repertoires related to play, positioning their interactions with journalists as a strategic balance between struggle and cooperation (Schohaus, Broersma, and Wijfjes 2017). Conversely, Francoeur (2016) found that Canadian journalists tap into multiple interpretive repertoires in articulating the ways in which they believe themselves to be different from public relations practitioners. Looking at the interpretive resources on which New Zealand journalists draw in writing about Maori people and issues, Matheson (2007, 93) identified a limited range, "repertoires of prejudice" difficult to overcome.…”
Section: How Journalists Talk About Journalism (And Themselves)mentioning
confidence: 94%